PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VIIIC SMPN 10 MALANG - Safitri, Nadidah; Sunarmi, Sunarmi; Suwono, Hadi (Jurnal Pendidikan Biologi, 2015)
Base on preliminary observations taken at VIIIC class of SMPN 10 Malang during 6th to October 31, 2014, were found several facts. Most of students test result have not reached minimum standard result that is 75 (only 14.17% of students who reach minimum standard result, and average of test results obtained by the students is 50), students are less skilled to do practical work, only certain students are active and enthusiastic in learning activities, some of these phenomenon are proof that motivation and student learning outcomes need to be improved. Solution that can be applied is to apply inquiry learning model. The purpose of this study is to obtain a clear explanation about the improvement of motivation and student learning outcomes at VIIIC class of SMPN 10 Malang through the implementation of inquiry learning model. This classroom action research was conducted at the time of learning by chapter of excretion system. Results of the research showed that, Students' motivation have increased from 72% in the first cycle to 82% in the second cycle. Cognitive learning outcomes of students have increased from 79.41% in the first cycle to 88.24% in the second cycle. Psychomotor learning outcomes of students have increased from 78% in the first cycle to 91% in the second cycle. Affective of learning outcomes of students have increased from 84% in the first cycle to 90% in the second cycle. Base on the data of these research, it can be concluded that the implementation of inquiry learning model can improve students motivation and learning outcomes at VIIIC class of SMPN 10 Malang.